EFFECT OF PLANTING DATES ON THE YIELD AND QUALITY OF GARLIC BY APPLICATION PLASTIC MULCH . - Amer Abdullah Hussein Al-juboori (Mesopotamia Journal of Agriculture, 2013)
ABSTRACT Experiment was carried out at the field of College of Agriculture and Forestry / University of Mosul During the growing season, autumn 2010 using RCBD Design with split system including two factors sowing dates (main plots) (1st October, 20th October, 10th November), and mulching (subplot)(Red polyethylene , yellow polyethylene, without cover) The results showed superiority of early planting dates on 1October and 20 October in most of the characteristics of vegetative growth and yield as compared with late planting in the 10 November which gave lower values in the high plant , number of leaves per plant, leaf area per plant , verdant yield per plant , head weight , and diameter , length , number of cloves , clove weight , and verdant and dry yield ton / hectare, the mulching has shown plants grown under Red Polyethylene superiority in all characteristics of vegetative growth and yield compared with cultivated without mulch, otherwise, the superior interaction treatment resulted from planted 20 October under the Red polyethylene in most vegetative characteristics and qualities of yield as compared with cultivated in 10th November and without mulching .